A review of the roles of men, women, and youth in ensuring food safety in the smallholder poultry value chain in Kenya - Garsow, Ariel V.; Kim, Erica G.; Colverson, Kathleen E.; Ilic, Sanja; Kunyanga, Catherine; Bainah, Abdiaziz; Kowalcyk, Barbara B. (Frontiers in Sustainable Food Systems, 2022)
Smallholder poultry production is a significant source of food and income for many rural households in Kenya, but poultry products can be contaminated with Salmonella and Campylobacter spp. Household members have different roles in poultry production, with women and youth more actively involved in the earlier steps of the value chain, such as poultry production and processing, particularly at the farm level. This literature review summarizes current knowledge and practices on the roles of women and youth in food safety in the smallholder poultry value chain in Kenya. Of the 19 articles identified, a majority referenced gender roles in the poultry value chain but few referenced youth or the roles of women and youth in ensuring food safety. Women and youth were found to be the primary smallholder poultry producers on-farm. Due to their direct involvement in poultry handling and production, women and youth may have higher potential risk of exposure to foodborne pathogens. Men, women, and youth were all found to participate in slaughtering and transportation of poultry products. It was also found that, although women may be the owners and caretakers of chickens, they may not have decision-making power on the use of income from the poultry, and poultry product sales. Therefore, women and youth may have limited decision-making power or access to resources, such as training, to increase food safety. Further research is needed to address the factors important to women and youth empowerment to ensure food safety in the smallholder poultry value chain and reduce the risks of foodborne disease in Kenya.